Integrated Sustainable Energy for Sub-Saharan Africa: A Case Study of Machinga Boma in Malawi - Juliana O. Eko; Manosh C. Paul (Energies, 2021)
Nearly 60% of the population of sub-Saharan Africa still live without access to electricity. Comparing the access rate of the countries in the region, Malawi ranks as one of the least electrified, with electricity available to only 14.6% of its population, as of 2018. This issue makes Malawi the case study of this research and poses the research question, “How can the low electricity access rate in Malawi be addressed?”. To address this research question, possible off grid, integrated, sustainable energy systems based on locally available energy resources—solar, wind, and diesel—are proposed. The multiyear and sensitivity analysis function of HOMER Pro microgrid simulation software is used to analyze the off grid performance of the proposed combinations of diesel generators, wind turbines, solar Photovoltaics, and battery storage, in providing power for an estimate of 400 households and nonresidential outlets in Machinga Boma, a community in the Southern region of Malawi. Based on the analysis, the Solar Photovoltaic/Diesel Genset/battery system combination consisting of 750 kWp solar Photovoltaic array, 460 kW (575 kVA) diesel generator and 3000 kWh nominal capacity battery bank is shown to be the most optimal system, with an overall energy cost of $0.339/kWh. Under the imposed design constraints and the sensitivity analysis performed to analyze the impact of changing the base fuel price, varying load growth, changing solar irradiation, and wind levels on the system performance, the most optimal system remained the preferred system choice.